ANALISIS WACANA BLACK CAMPAIGN (KAMPANYE HITAM) PADA PILPRES TAHUN 2014 DI MEDIA KOMPAS, JAWA POS DAN KEDAULATAN RAKYAT - La Januru (NATAPRAJA, 2016)
This thesis discusses black campaign discourse analysis (smear campaign) in the 2014 presidential election in the three media such as Kompas, Jawa Pos, and Sovereignty of the People. Discourse analysis in three media smear campaign by using the theory of critical discourse analysis (CDA) of Norman Fairclough. Research method in this research was discourse analysis. The study concluded that the practice of black campaign in the 2014 presidential election occurred in very high intensity, especially mediated-media both print and electronic media. It can be seen from the following indicators: first, the unhealthy campaign or unproductive as to demonize the other candidates. Second, the advertisement certainly has a tendency to attack (political attacks). Third, these ads do not have a clear source. Thus it can be said that these advertisement were problematic from any perspective. The messages in these ads were very provoking and does not give a good political education for the public.Keywords: Black Campain and Media.